TRACING THE EARLY EMERGENCE AND DEVELOPMENT OF THE CONCEPT OF HISTORICAL LITERACY IN THE 20TH CENTURY: Menelusuri Awal Kemunculan dan Perkembangan Konsep Literasi Sejarah Pada Abad ke-20 - Wildhan Ichzha Maulana; I Made Ratih Rosanawati; Fauzi Rachman; Ira Pramudawardhani; Miskawi (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Historical literacy studies have so far tended to focus on its implementation in schools, but the emergence and theoretical development of this concept in the 20th century have not been widely discussed. In fact, the conceptualization of historical literacy in the 20th century serves as a reference its implementation of historical literacy today in almost all schools worldwide, including in Indonesia. It adopts a qualitative library research method, then analyzes the data using Klaus Krippendorff's content analysis model, and strengthens the credibility of the data through source triangulation. The results illustrate that the concept of historical literacy was first formulated by Harry Scheiber in 1978, emphasizing the importance of in-depth knowledge of historical content. In 1989, Diane Ravitch also formulated a similar concept, emphasizing the importance of understanding and remembering the accumulation of historical facts (especially those related to official American history) to improve students' historical knowledge in America, which had declined drastically. In 1991, the concept of historical literacy was refined by Sam Wineburg, emphasizing the strengthening of historical methodological skills such as heuristics, verification, and contextualization. Meanwhile, in the context of current history learning in Indonesia, the concept of historical literacy formulated by Sam Wineburg is apparently relevant to the objectives of history learning in the ‘2013 Curriculum’ and the ‘Merdeka Curriculum’, which both emphasize historical thinking skills through research-based inquiry processes and strengthening historical literacy.